The Role of a Judge in Uncertain Times - Pleps Jānis (Baltic Journal of Law & Politics)
A judge’s mission is to protect the fundamental values of the liberal constitutional order: democracy, the rule of law, and human rights. The constitutional structure of democracy after the World War II is based on the presumption that the judges can fulfill this mission. The rise of populism and illiberal democracies, which challenge the liberal constitutional order, shows that judges are limited in the proper execution of this mission. Court packing is a crucial point in the building of illiberal democracies, and it should be avoided.